Impacto da suplementação de creatina sobre a força máxima, resistência à fadiga e função renal em praticantes de treinamento resistido - Vilar Neto, José de Oliveira (2018)
With the objective of investigating the effect of low dose supplementation of creatine monohydrate on maximal strength and fatigue resistance, it was also evaluated whether this supplementation could have some deleterious effect on renal function, 36 young male university students, training practitioners (age, 22.5 ± 4.3 years, height 1.76 ± 0.08 m, weight 77.0 ± 11.0 kg and BMI 24.6 ± 2.5 kg / m2) were randomly divided into three groups: placebo group (GP), group supplemented with 3 g / day of creatine (3G) and group supplemented with 5g / day creatine (5G). Participants performed tests to assess maximal strength (1RM) and fatigue strength of upper limbs (BFM) before and after 7, 14, 21, 28 and 35 days supplementing with creatine monohydrate or placebo and engaged in a standardized training program resisted (bodybuilding). Blood and urine samples were also collected before and after the 35-day intervention. Renal function was traditionally evaluated (GFR, serum urea and serum creatinine, proteinuria and albuminuria), and also, unprecedented for creatine users, from the latest biomarkers (KIM-1 and MCP-1). The results showed that the three groups showed a significant increase in maximal strength (1RM) after 35 days of intervention, however, the percentage increase in strength was about 100% higher in the groups supplemented with creatine (G3, Δ% 1RM = 20.0 ± 4.0, G5, Δ% 1RM = 19.9 ± 1.5) when compared to the placebo group (GP, Δ% 1RM = 10.3 ± 1.9). The resistance of the upper limbs showed significant improvement only for the 5G group, increasing from 39.9 ± 7.9 MAF / min to 50.7 ± 11.0 MAF / min after 35 days. The evaluation of renal function did not show any difference between the placebo group and the supplemented groups. These results corroborate previous findings where it was shown that creatine monohydrate supplementation is perfectly safe for renal health, and also effective for increasing maximal strength and resistance to fatigue of upper limbs.